Trends in referral pattern of antenatally diagnosed surgical abnormalities in a tertiary care center in North India - Prema Menon; Vineet Binu; Katragadda Lakshmi Narasimha Rao; Vanita Suri (Wolters Kluwer Medknow Publications, 2018)
Aim: Pregnant women with antenatally diagnosed surgical abnormalities of the fetus are often referred for pediatric surgical consultation for likely outcome and prognosis. In this study, we analyzed the gestational age at referral to see the benefits of the same in decision-making and also looked for any change in trends of referral pattern over a period with the increasing availability of ultrasonography (USG). Materials and Methods: Records of pregnant women referred for antenatal counselling over an eight year period were analyzed. This was an observational study conducted in the Pediatric surgery outpatient department of a tertiary care centre from 2008-2015. All pregnant women referred for antenatal counseling were included, with the diagnosis of fetal abnormalities being based on USG. Abnormalities were classified by system involved. Comparison of data before and after the year 2012 was done to look for change in trends. Patients with poor prognostic outcome were further analyzed. Results: A total of 1211 women were analyzed, with 490 (40.7%) presenting between 2008 and 2011 and 719 (59.3%) between 2012 and 2015. Overall, in those with likely poor prognostic outcome (n = 482), 189 (39.2%) patients presented at <20 weeks gestation, 106 (22%) between 21 and 24 weeks gestation, and 187 (38.8%) after 24 weeks of gestation. Genitourinary abnormalities (n = 220; 46%) accounted for the most common poor prognostic outcome group in all gestational ages. Conclusion: Nearly two-thirds (61%) of the patients with poor outcome were referred after 20 weeks of gestation, i.e., beyond the permissible time for termination. Fetal sonography expertise between 16 and 20 weeks should be improved as a priority by the government in peripheral centers.